A Cascadable Integrated Bistatic Six-port Transceiver at 60 GHz in a 130-nm BiCMOS Technology for SIMO-Radar Applications - Völkel, Matthias; Pechmann, Stefan; Hussein, Eissa Mohamed; Kissinger, Dietmar; Weigel, Robert; Hagelauer, Amelie Marietta (APMC, 2019)
In this paper a 60 GHz cascadable bistatic integrated interferometric transceiver for SIMO radar applications is presented. The integrated transceiver has been designed in a 0.13μm SiGe BiCMOS technology (SG13G2) from the institute innovations for high performance microelectronics (IHP). The System includes a 15 GHz buffer stage, a low noise amplifier, a passive interferometric six-port structure, several detectors and amplifiers as well as a digital interface. The chip has a size of 2.75mm x 1.15mm and a maximum power consumption of 525mW from a 3.3V power supply. The 15 GHz frequency input is multiplied to reach a 60 GHz signal at a minimum input power of -40 dBm. The chip delivers a maximum output power of 10.2 dBm. A digital interface adjusts the output power between -22 and 10,2 dBm at an output frequency of 60 GHz. The reference input power of the six-port and the RF input power could be adjusted in a range of 13.2 dB. The maximum P1dB is at -24.1 dBm. The measured power detector sensitivity is 7090 V/W. The standard deviation of the phase measurement is 0.025 rad.<br
Keywords: bistatic; industrial radar; integrated transceiver; interferometric radar; millimeter wave circuits; SIMO Radar; MMIC; SiGe BiCMOS; six-port; system-on-chip (SoC)